1998
DOI: 10.1093/ajcn/68.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Low dietary iron availability is a major cause of anemia: a nutrition survey in the Lindi District of Tanzania

Abstract: A nutrition survey was conducted in the rural Lindi District of Tanzania to determine the magnitude of anemia and iron deficiency in different age and sex groups as related to nutritional status, parasitic infections, food iron intake, and socioeconomic factors. In a 30-cluster sampling design, 660 households were randomly selected and a total of 2320 subjects aged 6 mo to 65 y were examined. Iron status was assessed by measuring hemoglobin and erythrocyte protoporphyrin in a finger-prick sample: 55% of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
3
11

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 32 publications
5
122
3
11
Order By: Relevance
“…No relationship was observed between schistosomiasis and anaemia, which is consistent with some other studies (Be®®-Mengue et al, 1993;Olsen et al, 1998), but differs from others (Tatala et al, 1998;Stoltzfus et al, 1997b). The present study was not designed to measure intensity.…”
Section: Stunting and Anaemia In African Schoolchildrensupporting
confidence: 91%
“…No relationship was observed between schistosomiasis and anaemia, which is consistent with some other studies (Be®®-Mengue et al, 1993;Olsen et al, 1998), but differs from others (Tatala et al, 1998;Stoltzfus et al, 1997b). The present study was not designed to measure intensity.…”
Section: Stunting and Anaemia In African Schoolchildrensupporting
confidence: 91%
“…SES, either defined by the type of school attended (ie public vs private), by the region of residence (ie rural vs urban) or by the level of parental education (primary school vs University), has been pointed out by many investigators, as an important determinant of the elevated prevalence of iron deficiency and iron deficiency anaemia among the less privileged school-aged children in developing countries (Soekarjo et al, 2001;Abalkhail & Shawky, 2002;Kilinc et al, 2002;Musaiger, 2002;Hashizume et al, 2003). Furthermore, the higher incidence of iron deficiency reported for adolescent schoolgirls, compared to boys (Tatala et al, 1998;Abalkhail & Shawky, 2002;Kilinc et al, 2002;Musaiger, 2002;Hashizume et al, 2004), shows that female gender exerts an extra effect on the prevalence of this medical condition, probably due to accessional iron losses through menstruation. The findings of the current study indicated that both SES and gender might need closer surveillance, in order to better understand the factors associated with the high prevalence of iron deficiency among urban schoolchildren in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency is probably the most prevalent and common micronutrient deficiency in the developing world today (Tatala et al, 1998;Asobayire et al, 2001;Abalkhail & Shawky, 2002;Hashizume et al, 2003). The detrimental public health effects of iron deficiency include anaemia, decreased intellectual and work performance as well as functional alterations of the small bowel (Oski, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient intake and poor bioavailability are major causes in developing countries [12][13][14] . Micronutrient content and bioavailability can be improved by either increasing the quantity of a micronutrient or increasing enhancing factors/decreasing inhibiting factors in foods using different techniques or sources.…”
mentioning
confidence: 99%